Determinación de los contaminantes producto de la combustión en el Parque automotor a diésel en el cantón Salcedo. - Amores Balseca, Alexandra Elizabeth (2018)
The present research had as purpose determine the possible atmosphere pollution generated by the incomplete combustion of the diesel fleet in Salcedo canton using the percentage of opacity. In Salcedo circulate around 1362 vehicles with diesel engine, to determine the current pollution of the area monitoring 148 vehicles and for the sampling points, chose the areas with the greatest influx of vehicles: Terrestrial Terminal, a public company of mobility of the Commonwealth of Cotopaxi, stop urban sprawl of the Mollehambato Huapante cooperative. During the first phase was carried out three measurements to each vehicles with the use of the Equipment AVL DITEST Gas Diesel 1000 with accessory 480 DISMOKE opacimeter which measures the opacity using the method of free acceleration as Ecuadorian Technical Standard NTE INEN 2202:2000. In the second phase, we monitored to transport units and we found that 61.5% of the vehicles sampled exceed the maximum limits allowed (LMP) opacity of emissions for mobile sources with diesel engine that is DOES NOT FULFILLS with the Ecuadorian Technical Standard NTE INEN 2207:2002, leading to a deterioration in the air quality of the population affecting human health of atmospheric pollution. With the results obtained will enable local and national authorities responsible for the management and environmental quality, to take measures that will help to improve the quality of air.